135 Clinical impact of a structured daily staff meeting in an emergency department. (23rd September 2015) - Steinmetz, J P; Bilbault, P; Gicquel-Schlemmer, B; Christophe, B; Duja, C M; Kauffmann, P; Mihalcea, M; Geronimus, C; Kam, C; Kopferschmitt, J
Abstract : Context and Objectives: The emergency department is a sector with an important clinical exposure in connection with the required quality of care. This is due to the great number of patients seen every day, the variety of clinical situations met and the multiplicity of colleagues involved. The daily staff meeting with the team coming out of duty is an important moment for the continuation of care (hand over, diagnosis and/or treatments readjusted, organisation of the daily department activity, notified dysfunctional issues), but also for training purpose towards the juniors of the team. The new protocol was put in place in October 2006 after we noticed the lack of structure and the excess of verbal exchanges in the meetings. The objectives were the followings: more formal organisation of the meeting in terms of timing and components, improve the quality of hand over (verbal and written), leave a written trace of the decisions and the benefit-risk discussion made by the staff, track down and handle the dysfunctional issues, survey how the patient's records are kept, discuss the topics which will be developed in priority for the education and training of the junior members of the team. Schedule: Internal regulations have been written, summed up in an eight points check-list (daily task distribution, hand over, dysfunctional issues, information about the admitted patients, position of each staff member during the day in the department, patient's records keeping…) used by the moderator. At the beginning of each meeting a moderator and a secretary are designated amongst the seniors of the team. A printed sheet is used, one per day. At the end of the meeting, the secretary transfers the predefined key elements on a data base. The results will be shown from to day to day on graphics automatically updated (number of patients admitted, number and type of dysfunctional issues, missing criteria in keeping patient's records, etc). A special dating stamp is used in the patient's records to underline the decisions made and the benefit-risk discussions. According to the case, the dysfunctional issues are dealt with immediately or discussed later at the debriefing meetings. These meetings, held every 2 months, are formally summarised in a report distributed to the different actors involved. Once these data have been surveyed, an agenda of improvement actions is defined and each theme will be allocated to one of the senior colleagues. An indicator follow up is scheduled and a synthetic assessment is established annually. Results: After 3 years, 98% of the structured staff meetings were following the protocol. Most of the meetings didn't last longer than the fixed 45 min. Thanks to the collection of the dysfunctional issues a number of improvement actions are put in place, punctual or general actions, development of clinical pathways, procedures, protocols. Audits were realised as well as practise enquiries or relevance analysis. During these staff meetings about 50 patient's notes have been annually analysed. The main improvements were about the indicators to keep patient's records accurate, particularly in keeping trace of prescriptions, pain control evaluation as well as the quality of the discharge letter. Discussion: The main positive aspect of the structured staff meeting is the full support and interest of the professionals, the educational approach, the improvement of the overall quality of the patient's records. Remaining key points need to be improved: the way to keep daily notes exhaustive, the best way to communicate about the data base and to make individual and collective work more valuable. Conclusion: The daily structured staff meeting seems to be adjustable and adapted to the activity of an emergency department. However, a large consensus is required from the team to keep up the ability for such a tool to evolve. Contexte, objectifs: Le service des Urgences est un secteur clinique à haut risque. La qualité de la prise en charge du patient peut y être mise en défaut de par le nombre important de passages quotidiens, le polymorphisme des situations cliniques et la multiplicité des intervenants. La réunion quotidienne, au sortir de garde, est un temps capital pour la continuité des soins, l'organisation de l'activité, mais aussi pour la formation des médecins « juniors » de l'équipe. La constatation d'une réunion peu structurée où prévalait la tradition orale nous a décidé à mettre en place en octobre 2006 un staff protocolé, dont les objectifs sont: de formaliser la conduite de la réunion dans sa durée et ses composantes, d'optimiser la qualité des transmissions, de réajuster le diagnostic et/ou les orientations thérapeutiques, de tracer systématiquement les décisions du staff et, le cas échéant, la réflexion bénéfice-risque, de dépister et traiter les dysfonctionnements, d'évaluer la tenue des dossiers, de dégager les priorités de formation pour les membres juniors de l'équipe. Programme: Un règlement intérieur a été rédigé, résumé en une check-list de 8 points (répartition de l'activité pour la journée, transmissions, dysfonctionnements, retour d'information, tenue du dossier…) à la disposition du modérateur. Un modérateur et un secrétaire sont désignés pour chaque séance parmi les médecins « seniors ». Une fiche est remplie par jour. En fin de réunion, le secrétaire en reporte dans une base de données les éléments-clés pré-définis. Ces résultats apparaissent au jour le jour sous forme de graphiques incrémentés automatiquement (nombre de patients hospitalisés, nombre et type de dysfonctionnements, critères manquant dans la tenue du dossier, etc.) L'utilisation d'un tampon-dateur incite à noter systématiquement, dans le dossier, les décisions prises et la réflexion bénéfice-risque. Selon les cas, les dysfonctionnements sont traités immédiatement ou discutés ultérieurement lors des réunions bimestrielles de débriefing. Celles-ci donnent lieu à un compte-rendu formalisé et diffusé aux acteurs concernés. A l'issue de l'étude de ces données, un calendrier d'actions d'amélioration est défini et un pilote (médecin senior) est identifié pour chaque thème retenu. Un suivi d'indicateurs est programmé et un bilan de synthèse est établi annuellement. Résultats: Avec un recul de 3 ans, le protocole du staff a été respecté dans 98% des cas. Il n'a dépassé que rarement la durée fixée à 45 min. Le recueil des dysfonctionnements a permis la mise en place de nombre d'actions d'amélioration ponctuelles ou systémiques, l'élaboration de chemins cliniques, de procédures, de protocoles, la réalisation d'audits, d'enquêtes de pratiques ou d'analyses de pertinence. Une cinquantaine de dossiers sont analysés annuellement lors de ces staffs. Les améliorations ont porté sur l'ensemble des indicateurs de tenue du dossier, notamment sur la traçabilité (prescriptions, prise en charge de la douleur) et la présence et la qualité de la lettre de sortie. Discussion: Les principaux éléments positifs de la mise en place de ce staff protocolé sont l'adhésion et la participation des professionnels, la démarche pédagogique, l'augmentation de la traçabilité globale dans le dossier patient. Des points restent à améliorer : la qualité et l'exhaustivité de saisie des fiches quotidiennes, les modalités de communication des résultats obtenus et la valorisation des efforts individuels et collectifs. Conclusion: Le staff protocolé quotidien apparaît comme un outil modulable et adapté à l'activité des urgences. Cependant un large consensus dans l'équipe est un pré-requis pour son appropriation et son évolutivité.